SECURE IoT TECHNOLOGY STACK - Іськович, Тарас; Коробейнікова, Тетяна (SWorldJournal, 2023)
This paper is devoted to existing solutions analysis of building a secure technological stack for the Internet of Things (IoT). As a result, a matching of selected known technologies was created according to the security approach to the IoT organization.